Analysis of Dynamic Buffer Management Approaches in Mobile Ad hoc network (International Journal of Engineering and Computer Science, 2017)
Mobile ad hoc network also known as wireless ad hoc network is one of the most popular network technologies in research and development. The ad hoc nature of network keep attracted researchers and engineers for finding the new and enhance techniques. This paper presents a analysis on mobile ad hoc network and the buffer management technique. Therefore the paper includes the MANET details, buffer management techniques, recent research work centered on buffer management and a proposal for improving the network performance by incorporating the buffer management in MANET.